MAPEAMENTO GEOMORFOLÓGICO DE DETALHE - UMA PROPOSTA DE ASSOCIAÇÃO ENTRE O MAPEAMENTO TRADICIONAL E AS NOVAS TÉCNICAS EM GEOPROCESSAMENTO - Rodrigues, Sílvio Carlos; Brito, Jorge Luís Silva (Caminhos de Geografia, 2000)
This paper presents the results of the mixed techniques of traditional geomorphological cartography, in special an interpretation of stereo pairs and geoprocessing techniques, using Spring Software. This technique permits a more quickness in elaboration